Pengaruh Metode Reading, Presenting, and Questioning (RPQ) dan Metode Experimenting and Discussion (ED) Terhadap Hasil Belajar Kognitif Ditinjau dari Pengetahuan Awal Siswa - Ollyvia Ika Prastiwi; Widodo Widodo; Ishafit Ishafit (Radiasi : Jurnal Berkala Pendidikan Fisika, 2020)
Learning methods are needed so that students are more active in learning, as Reading, Presenting and Questioning (RPQ), and the Experimenting Discussion (ED) method. The purpose of this study is 1) to find out whether there are differences in cognitive learning outcomes with the RPQ and ED methods in terms of students' initial knowledge. 2) To determine whether there is influence of cognitive learning outcomes by the RPQ and ED methods without students' initial knowledge This type of research is a quasi-experimental design with pretest-posttest control group design. The study population was all eighth grade students. This study uses a clusser random sampling technique in sampling. The study sample was students of class X Mia 1 as experimental class I and X Mia 3 as experimental class II. The data collection technique used is a test. Research instruments include RPP, Physics Articles, LKPD, and Pretest and Posttest Questions. Based on the results of the study using a childova test assisted by SPSS 23 software, it was obtained 1) Significant value was obtained at 0.001 and smaller than 0.05 so it was rejected, meaning that there were differences in students 'cognitive learning outcomes using the RPQ method and ED method in terms of students' initial knowledge. Significant value obtained by eliminating the covariate variable (initial knowledge) is 0.088 and greater than 0.05, it is accepted, meaning that there is no effect on students 'cognitive learning outcomes using the RPQ method and ED method without the students' initial knowledge. Based on the analysis it can be concluded that the initial knowledge used as an influential covariate variable on students' cognitive learning outcomes on the use of the RPQ and ED methods.